Perancangan Media Belajar Mandiri Berbasis Canva Pada Mata Pelajaran Pendidikan Agama Islam Untuk Siswa Sma N 1 Matur - Ahmad Zulkarnain Nasution; Hari Antoni Musril; Sarwo Derta; Tasnim Rahmat (Yayasan Lembaga Studi Makwa, 2025)
This research was motivated by the use of learning media that has not yet supported the learning process of Islamic Religious Education at SMA N 1 Matur. Based on interviews conducted by the author with teachers and students, it was found that the learning media used in Islamic Religious Education consisted of printed books, blackboards, and the teaching method was mostly lecture-based. The use of computer technology in education not only facilitates the learning process but also opens up new opportunities for innovation and more interactive self-directed learning. By using digital platforms such as Canva in the development of learning media, teachers can present materials in a more engaging and easily understood manner for students. Based on the results of observations and interviews with Islamic Religious Education (PAI) teachers at SMA N 1 Matur, it was found that the use of digital learning media is still limited and predominantly relies on lecture methods and textbooks. This condition causes students to be less active in the learning process and less motivated to study independently. This study uses the Research and Development (R&D) model with the Hannafin and Peck approach, which consists of three stages: needs analysis, design, and implementation. The developed product was tested for its validity, practicality, and effectiveness. The validity test results showed that the developed media fell into the